Pendampingan Pendidikan Anak Usia Dini (PAUD) Cahaya Bunda di Jembatan Merah Kota Surabaya - Abidin, Ratno; Rahayu, Aristiana Prihatining (Universitas Muhammadiyah Surabaya, 2017)
Community service activities in the red bridge ridge Kelurahan Nyamplungan District Pabean Cantika Surabaya. They reside with sober, even they can say their homes are roofed by the earth, meaning they only sleep in the grove of shops or warehouses that potluck often expelled by SATPOL PP. Their work scavenging, begging and ngamen in a red light stop, shops in the market Kapasan Kota Surabaya. So far, they are not recognized by Surabaya city government because they do not have identity card and family card. Though it is located in Jempatan Merah It has been many years even since birth. Seeing their difficulty to get rights and recognition from Surabaya City Government and get the feasibility of life. The team in cooperation with Muhammadiyah Branch Chief of Surabaya City has been helping residents living on the banks of the Jembatan Merah river. Programs that have been dilaksanaka Pengajian, Al Quran Educational Place, Early Childhood Education, learning to read, write and make craft.Permasalahan main in Child Street Stewardship and Blind Literacy In the Red Bridge Kelurahan Nyamplungan Kecamatan Pabean Cantika Kota Surabaya.